Intact Reflexive but Deficient Voluntary Social Orienting in Autism Spectrum Disorder - Kirchgessner, Megan A.; Chuang, Alice Z.; Patel, Saumil S.; Sereno, Anne B. (Frontiers in Neuroscience, 2015)
Impairment in social interactions is a primary characteristic of people diagnosed with autism spectrum disorder (ASD). Although these individuals tend to orient less to naturalistic social cues than do typically developing (TD) individuals, laboratory experiments testing social orienting in ASD have been inconclusive, possibly because of a failure to fully isolate reflexive (stimulus-driven) and voluntary (goal-directed) social orienting processes. The purpose of the present study was to separately examine potential reflexive and/or voluntary social orienting differences in individuals with ASD relative to TD controls. Subjects (ages 7-14) with high-functioning ASD and a matched control group completed three gaze cueing tasks on an iPad in which individuals briefly saw a face with averted gaze followed by a target after a variable delay. Two tasks were 100% predictive with either all congruent (target appears in gaze direction) or all incongruent (target appears opposite from gaze direction) trials, respectively. Another task was non-predictive with these same trials (half congruent and half incongruent) intermixed randomly. Response times (RTs) to the target were used to calculate reflexive (incongruent condition RT – congruent condition RT) and voluntary (non-predictive condition RT – predictive condition RT) gaze cueing effects. Subjects also completed two additional non-social orienting tasks (ProPoint and AntiPoint). Subjects with ASD demonstrate intact reflexive but deficient voluntary gaze following. Similar results were found in a separate test of non-social orienting. This suggests problems with using social cues, but only in a goal-directed fashion, in our sample of high-functioning individuals with ASD. Such findings may not only explain inconclusive previous findings but more importantly be critical for understanding social dysfunctions in ASD and for developing future interventions.